Current innovative treatments of obesity - Wach, Damian; Głaz, Aneta; Wiśniewska, Jolanta; Radziejowska, Zuzanna (Journal of Education, Health and Sport, 2023)
Obesity is a complex and pervasive chronic health concern with multifaceted origins in which abnormal or excessive fat accumulation worsens health, increases the risk of long-term medical complications and shortens life expectancy. It is associated with type 2 diabetes, non-alcoholic fatty liver disease (NAFLD) and cardiovascular disease. More than 603.7 million adults are estimated to be obese. The cause of obesity is a long-term energy imbalance caused by a combination of increased energy intake and decreased energy expenditure. The purpose of this study is to analyze the effectiveness of modern obesity treatments such as intermittent fasting, semaglutide and surgical interventions. Intermittent fasting involves voluntary periods of restricted or zero caloric intake at specified intervals. However, research results on the effectiveness of this dietary strategy are conflicting. The findings indicate that incorporating physical exercise can further enhance the outcomes of applying this diet. Semaglutide, a GLP-1 (glucagon-like peptide-1) analog, has shown efficacy in promoting weight loss among adults and adolescents, along with metabolic and cardiovascular improvements. Laparoscopic sleeve gastrectomy (LSG) is a common bariatric procedure, while Roux-en-Y gastric bypass (LRYGB) is another option. Long-term studies show that both methods effectively promote weight loss. In conclusion, obesity is a multifaceted condition that requires a comprehensive treatment approach. Individualized strategies including dietary changes, pharmaceutical interventions such as semaglutide, and surgical options can together contribute to effective weight management and improved health outcomes.